The Relationship Between Gout Arthritis Pain and the Level of Independence in Daily Life of Patients at Helvetia Health Center - Ritha Mariati Sembiring; Eka Permata Sari Br. Sihombing; Indah Juni Florida Daeli; Maria Aloysia O. W. L. Masa; Grace Krishna Angelica Gea; Laura Fernadia Purba (Pusat riset dan Inovasi Nasional, 2026)
Gout arthritis is a disease characterized by sudden inflammation of the joints due to high levels of uric acid in the body (hyperuricemia). This condition is marked by acute episodes of joint inflammation, often affecting a single joint and preceded by asymptomatic periods of varying duration. Older adults represent the final stage in the human lifespan and experience the natural aging process. This study employed an analytic survey design with a cross-sectional approach. The purpose of this study was to determine the relationship between gout arthritis pain and the level of independence in activities of daily living among patients at the Helvetia Public Health Center. The results showed that the majority of older adults in the working area of UPT Puskesmas Helvetia experienced high levels of pain, with 73 respondents reporting severe pain. Meanwhile, most respondents demonstrated independence in their daily activities, with 72 categorized as independent. The findings indicate a significant relationship between gout arthritis and the level of independence in activities of daily living among older patients at the Helvetia Public Health Center.